Policy-based Contracting in Semantic Web Service Markets - Lamparter, Steffen (Studies on eOrganisation and Market Engineering, 2007)
This book presents an interdisciplinary approach drawing from the fields of computer science, economics, and law to realize dynamic and flexible Web service markets. It thereby addresses technical issues such as the functional and non-functional description of Web services, economic questions like selecting the right service at an acceptable price, and legal problems dealing with automated contract conclusion and interpretation.